Menggali Keutamaan Al-Qur’an Sumber Petunjuk Dalam Kehidupan Umat Islam - Sifa Hayatul Husna; Elsita Insani; Najwa Ananda Putri; Sabila Ramadani Lubis; Latifha Umi Barokha; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine that the Qur'an as the holy book of Muslims plays an important role in guiding daily behavior and actions. In the context of modern life full of challenges, a deep understanding of the Qur'an as the main source of guidance is very crucial to shape the character and moral values ​​of Muslims. The purpose of this study is to explore the primacy of the Qur'an as the main source of guidance in the lives of Muslims. The method used for the study on